The inverse relation between changes in body weight and serum phosphate expresses weight loss after lifestyle intervention in non-smokers and smokers, but not in subjects who quit smoking - Håglin, Sofia; Bäckman, Lennart; Håglin, Lena (Frontiers in Nutrition, 2026)
Background/objectivesMetabolic alterations, physical activity, and dietary pattern together can explain why smoking cessation (SC) often results in weight gain. We studied changes in weight and changes in cardiovascular (CVD) risk factors after an intervention that included an exercise program, dietary advice, and stress management.Subjects/methodsThe patient population (n = 1,782) attended the Vindeln Patient Education Centre (VPE-center) for a 4-week comprehensive lifestyle intervention program, which included the option of smoking cessation. The data were collected before and after, at either the 6- or 12-month follow-up on 247 smokers, 95 former smokers, and 1,440 non-smokers.ResultsA high CVD-risk population lost weight and had decreased serum triglyceride (S-TG) and increased serum phosphate (S-P) at the 6- or 12-month follow-up. At baseline, smokers and former smokers had higher S-TG and lower systolic blood pressure (SBP) than non-smokers. Smokers had higher S-P at baseline and higher S-TG at follow-up than non-smokers. A daily energy intake of around 6,300 kJ (1,500 kcal) and a schedule of physical activity resulted in weight loss, but to a significantly lesser extent in patients who quit smoking compared to patients who continued to smoke or stayed as non-smokers. With SC, a decrease in S-P was associated with weight gain, whereas an increase in S-P was associated with weight loss.ConclusionAn interaction between smoking habits, body mass index (BMI), and S-P may express a metabolic change that contributes to the degree of weight loss. Differences in changed metabolic response according to smoking habits express effects from smoking cessation, besides differences in the amount of weight change.